Chemical synthesis of graphene oxide and graphene - Soh, Kian Bin. (2010)
Graphene oxide (GO) was first synthesized using a modified Hummers method. The success of the synthesis was affirmed by using Atomic Force Microscopy (AFM) to find out the experimental values of GO and then comparing it with values obtained from other research papers.